Agreement attraction in comprehension: Representations and processes - Wagers, Matthew W.; Lau, Ellen F.; Phillips, Colin (Journal of memory and language, 2009)
Much work has demonstrated so-called attraction errors in the production of subject–verb agreement (e.g., ‘The key to the cabinets are on the table’, [Bock, J. K., & Miller, C. A. (1991). Broken agreement. Cognitive Psychology, 23, 45–93]), in which a verb erroneously agrees with an intervening noun. Six self-paced reading experiments examined the online mechanisms underlying the analogous attraction effects that have been shown in comprehension; namely reduced disruption for subject–verb agreement violations when these ‘attractor’ nouns intervene. One class of theories suggests that these effects are rooted in faulty representation of the number of the subject, while another class of theories suggests instead that such effects arise in the process of re-accessing subject number at the verb. Two main findings provide evidence against the first class of theories. First, attraction also occurs in relative clause configurations in which the attractor noun does not intervene between subject and verb and is not in a direct structural relationship with the subject head (e.g., ‘The drivers who the runner wave to each morning’). Second, we observe a ‘grammatical asymmetry’: attraction effects are limited to ungrammatical sentences, which would be unexpected if the representation of subject number were inherently prone to error. We argue that agreement attraction in comprehension instead reflects a cue-based retrieval mechanism that is subject to retrieval errors. The grammatical asymmetry can be accounted for under one implementation that we propose, or if the mechanism is only called upon when the predicted agreement features fail to be instantiated on the verb.